Core–Sheath Stretchable Conductive Fibers for Safe Underwater Wearable Electronics. Issue 1 (1st December 2019) - Zhang, Yan; Zhang, Weifeng; Ye, Guo; Tan, Qishuo; Zhao, Yan; Qiu, Jiakang; Qi, Shuyan; Du, Xiaojia; Chen, Tinglei; Liu, Nan
Abstract: Stretchable conductive fibers can be directly woven into textiles and applied in wearable and implantable electronic devices. However, for a stretchable conductive fiber that is capable of safely using in full water environment with strains when contacting to skin, it is challenging. Herein, an ultrafine core–sheath stretchable conductive fiber (CSCF in short) with insulative outer sheath and conductive inner core is designed particularly for safe underwater electronic skin devices. CSCF starts from prestrained Lycra fiber followed by spray coating 1D conductive species (carbon nanotubes (CNTs)/silver nanowires (AgNWs)) and wrapping styrene‐(ethylene‐butylene)‐styrene (SEBS) thin film. CSCF exhibits stable core conductivity (e.g., R 0 ≈ 2 × 10 4 S m −1, Δ R/R0 ≈ 0.1 at 100% strain) as well as surface insulation upon mechanical stretching in full water environment. The thickness‐tunable SEBS not only protects skin away from leak of CNTs and AgNWs, but also efficiently suppresses leakage current to an extremely safe level (<1 µA at 5 V) when applying in underwater electronic skin devices. A wireless charging patch composed by CSCF induction coil is able to light light emitting diode (LEDs) no matter when CSCFs are folding and stretching in water. These advantages highlight the promising application of stretchable conductive fiber with protective polymer skin for safe underwater wearable electronics. Abstract : Here, presented is a core–sheath stretchable conductive fiber (CSCF) for safe underwater wearable electronics. The styrene‐(ethylene‐butylene)‐styrene (SEBS) skin in CSCF can efficiently protect conductive species from damage and keep CSCF being safe to human in water. CSCF can light LED at stretching in water by wireless charging and be continuously dipped in water for 10 days without significant changes in conductive performance.